2017
DOI: 10.1111/inr.12425
|View full text |Cite
|
Sign up to set email alerts
|

Job stress in new nurses during the transition period: an integrative review

Abstract: Findings of this review may provide valuable input to assist nurse administrators in developing and implementing organizational measures to reduce stress in new nurses while maximizing and facilitating their integration into the nursing workforce. Such measures may include the following: establishment of a well-structured transition programme, provision of an adequate orientation and senior staff mentorship, stress management programmes, in-service educational programmes and exposure to clinical simulation sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 44 publications
4
92
0
4
Order By: Relevance
“…In the current study, novice nurses reported frustration over the lack of support provided by the organization and their colleagues. This is not surprising considering the current situation in most rural areas in the Philippines, where most of the government hospitals are located; these hospitals are lacking in terms of structured hospital policies, ward processes, and programs to support the transition and professional growth of new nurses . This finding is additionally similar to those of international studies highlighting organizational support as being inadequately provided to new nurses during this critical period …”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In the current study, novice nurses reported frustration over the lack of support provided by the organization and their colleagues. This is not surprising considering the current situation in most rural areas in the Philippines, where most of the government hospitals are located; these hospitals are lacking in terms of structured hospital policies, ward processes, and programs to support the transition and professional growth of new nurses . This finding is additionally similar to those of international studies highlighting organizational support as being inadequately provided to new nurses during this critical period …”
Section: Discussionsupporting
confidence: 69%
“…In one study, new nurse felt pressured and stressed due to the unrealistic expectations set by their senior nurses along with added responsibility of supervising nursing students, which have contributed further to their feelings of transition shock . Other factors known to contribute to stress experiences among new nurses included unreasonable workloads, performing unfamiliar procedures, caring for patients with complex conditions, having interactions with other health care team members, handling hospital equipment, and a lack of communication skills …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly in China, newly graduated nurses working in a pharmacy admixture service reported that lack of professional nursing competence was the main source of their stress followed by heavy workloads and the sociological environment (Wang et al, 2015). Although the relationships need further exploration (Labrague and McEnroe-Petitte, 2018), evidence show that some individual and organizational factors such as female gender, low family income, and shift might contribute to nurses' stress experiences and well-being (Jones et al, 2015;Alzayyat and Al-Gamal, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…explored the experiences of new nurses during transition, andKe et al, (2017),Oosterbroek (2017) andWard & McComb (2017) focused on preceptorship Olejniczak et al (2010). provided an overview of the evidence base linked to simulation as an orientation strategy for NQNs, whilst three reviews (Edwards et al(2015),Gardiner & Sheen (2016) and Pasila et al (2017) examined broader supportive approaches.Where experiences of NQNs were discussed as part of a review, it was clear that transition from student to Registered Nurse is stressful(Labrague & McEnroe-Petitte, 2017; Gardiner & Sheen, 2016) Labrague & McEnroe-Petitte (2017). identified the main causes of stress were workload and a perceived lack of competence.The need for a supportive environment providing NQNs with learning opportunities and constructive feedback was identified by Gardiner & Sheen (2016),Oosterbroek (2017) andOlejniczak (2010) who also found simulation could play an role in orientating new nurses, allowing for learning in a safe environment.Benefits of preceptorship were discussed byWard & McComb (2017),Ke et al (2017),Oosterbroek (2017), and Pasila et al (2017).Edwards et al (2015) explored the impact of a broader range of interventions: preceptorship; mentorship; and internship.…”
mentioning
confidence: 99%